Paradigm of Biased PAR1 (Protease-Activated Receptor-1) Activation and Inhibition in Endothelial Cells Dissected by Phosphoproteomics. Issue 10 (October 2017) - van den Eshof, Bart L.; Hoogendijk, Arie J.; Simpson, Pelle J.; van Alphen, Floris P.J.; Zanivan, Sara; Mertens, Koen; Meijer, Alexander B.; van den Biggelaar, Maartje
Abstract : Objective—: Thrombin is the key serine protease of the coagulation cascade and mediates cellular responses by activation of PARs (protease-activated receptors). The predominant thrombin receptor is PAR1, and in endothelial cells (ECs), thrombin dynamically regulates a plethora of phosphorylation events. However, it has remained unclear whether thrombin signaling is exclusively mediated through PAR1. Furthermore, mechanistic insight into activation and inhibition of PAR1-mediated EC signaling is lacking. In addition, signaling networks of biased PAR1 activation after differential cleavage of the PAR1 N terminus have remained an unresolved issue. Approach and Results—: Here, we used a quantitative phosphoproteomics approach to show that classical and peptide activation of PAR1 induce highly similar signaling, that low thrombin concentrations initiate only limited phosphoregulation, and that the PAR1 inhibitors vorapaxar and parmodulin-2 demonstrate distinct antagonistic properties. Subsequent analysis of the thrombin-regulated phosphosites in the presence of PAR1 inhibitors revealed that biased activation of PAR1 is not solely linked to a specific G-protein downstream of PAR1. In addition, we showed that only the canonical thrombin PAR1 tethered ligand induces extensive early phosphoregulation in ECs. Conclusions—: Our study provides detailed insight in the signaling mechanisms downstream of PAR1. Our data demonstrate that thrombin-induced EC phosphoregulation is mediated exclusively through PAR1, that thrombin and thrombin–tethered ligand peptide induce similar phosphoregulation, and that only canonical PAR1 cleavage by thrombin generates a tethered ligand that potently induces early signaling. Furthermore, platelet PAR1 inhibitors directly affect EC signaling, indicating that it will be a challenge to design a PAR1 antagonist that will target only those pathways responsible for tissue pathology. Abstract : Supplemental Digital Content is available in the text.